Assessing Specific Intervention Programs to Address Stunting Using OECD-Criteria - Afrilia, Nella; Wijayanti, Nanda Ayu (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This study aims to evaluate and provide recommendations for improvements in the implementation of the stunting intervention program in 2023 by the local government, using the program evaluation criteria developed by the OECD. The government of XYZ Regency is selected as the unit of analysis, considering that the prevalence of stunting in XYZ Regency has not yet reached the RPJMN target for the period of 2020 to 2024. Additionally, there were findings from the BPK (Audit Board of Indonesia) regarding the budgeting for stunting handling. This research uses a qualitative method with a case study approach to thoroughly study the organization over a specified period. This study utilizes an evaluation case study (Ellet, 2018) to assess the effectiveness of the stunting intervention program and provide suggestions for improvements. The analytical method used to answer the research questions is descriptive analysis. This research method is expected to facilitate understanding and evaluation of the program according to the OECD Evaluation Criteria (2021). The analysis results can be used to draw conclusions, identify obstacles, and offer solutions. The evaluation of the specific stunting intervention program in XYZ Regency shows that the program has not yet met the OECD-DAC criteria. Therefore, improvements are needed to ensure that the intervention program can effectively contribute to the acceleration of stunting reduction.